PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X-4 SMA NEGERI KEBAKKRAMAT TAHUN PELAJARAN 2014/2015 - Septariana Arlinta Putri; Yudi Rinanto; Marjono Marjono (Universitas Sebelas Maret, 2015)
This study was aimed to improve the students critical thinking ability of the biology student in X-4 SMA Negeri Kebakkramat academic year 2014/2015. This research was a class action research which consists of three cycles. Each cycle contains planning, implementing, observing and reflecting. The subject of this research was the student in X-4 SMA Negeri Kebakkramatand the amount was 36. The data collecting techniques of this research are test critical thinking ability, observation, interview and documentation. The data validation of this research was triangulation method. The data were analyzed by qualitative description techniques. The result shows that student critical thinking ability is increased in Pre-cycle, Cycle I, Cycle II, and Cycle III. Interpretation aspect increase from 42,36% to 95,14%; inference aspect increase from 56,94% to 83,33%; evaluation aspect increase from 58,33% to 95,14%; explanation aspect increase from 49,31% to 95,14%; analyze aspect increase from 59,72% to 88,89%; self-regulation aspect increase from 46,53% to 95,75%. This research’s conclution is the implementation of Problem Based Learning can improve critical thinking ability of the student in X-4 SMA Negeri Kebakkramat academic year 2014/2015. Keywords: Problem Based Learning, Critical Thiking